Disclosure Information on Indonesian UMKM Taxes - Prihanto, Hendi; Damayanti, Prisila (Program Studi Akuntansi FPEB UPI, 2020)
Abstract. This research aims to obtain evidence and explain the relationship between tax rates, awareness, understanding, and morale of moderated taxpayers with business prospects to disclose tax information. the study was conducted using MSME subjects in the Kebayoran Baru South Jakarta Blok M market area as the largest trading center in DKI Jakarta, with research object PP 23 of 2018. There were 230 questionnaires distributed, but after the obligations and duties of 206 appropriate questionnaires filled out by MSME entrepreneurs Data analysis using multiple linear regression and moderated regression analysis (MRA), through testing the validity and reliability of research instruments. The results showed that tax rates, awareness, understanding, and morals have a positive and significant effect on tax disclosure by MSME taxpayers, as well as unfavorable business prospects able to moderate by lowering the significance value of the effect of tax rates, awareness, understanding, morals on their tax disclosures. This research contributes to the government regarding the effectiveness of the application of PP tariffs in 2018 through several variables used by researchers, as well as theoretical development of factors that affect tax disclosure.